2018
DOI: 10.1249/mss.0000000000001441
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Ingestion Attenuates Fatigue-induced Loss of Muscle Torque Complexity

Abstract: Caffeine ingestion slowed the fatigue-induced loss of torque complexity and increased the time to task failure during intermittent isometric contractions, most likely through central mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 37 publications
10
77
0
Order By: Relevance
“…Common synaptic input to muscles and motor unit synchronization have been proposed to be major determinants of force variability (Dideriksen, Negro, Enoka, & Farina, ; Farina & Negro, ) and have been demonstrated to increase with fatigue (Castronovo, Negro, Conforto, & Farina, ). We have, therefore, previously speculated a link between motor unit synchronization and torque complexity (Pethick et al., , ). However, direct measurement of individual motor units via high‐density surface EMG electrodes will be necessary to confirm a link between motor unit synchronization and torque complexity, rather than the analysis of motor unit action potential trains recorded using bipolar EMG, as was done in the present study.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Common synaptic input to muscles and motor unit synchronization have been proposed to be major determinants of force variability (Dideriksen, Negro, Enoka, & Farina, ; Farina & Negro, ) and have been demonstrated to increase with fatigue (Castronovo, Negro, Conforto, & Farina, ). We have, therefore, previously speculated a link between motor unit synchronization and torque complexity (Pethick et al., , ). However, direct measurement of individual motor units via high‐density surface EMG electrodes will be necessary to confirm a link between motor unit synchronization and torque complexity, rather than the analysis of motor unit action potential trains recorded using bipolar EMG, as was done in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Several computer simulation studies have suggested that increased motor unit synchronization substantially increases EMG amplitude (Yao, Fuglevand, & Enoka, ; Zhou & Rymer, ). Moreover, motor unit synchronization has previously been speculated to be a potential cause of the fatigue‐induced loss of torque (Pethick et al., , ) and EMG (Beretta‐Piccoli et al., ; Mesin, Cescon, Gazzoni, Merletti, & Rainoldi, ) complexity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently observed that caffeine ingestion attenuates the development of central fatigue (assessed using the twitch interpolation technique) and the fatigue‐induced loss of torque complexity, independently of the development of peripheral fatigue (Pethick, Winter, & Burnley, ). This suggests that the central processes make a small, but significant, contribution to the fatigue‐induced loss of torque.…”
Section: Introductionmentioning
confidence: 99%